2020
DOI: 10.1017/s0033291720000525
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine: prospective novel therapy for depression and PTSD

Abstract: BackgroundDepression and post-traumatic stress disorder (PTSD) are leading causes of disability and loss of life by suicide. Currently, there are less than satisfactory medical solutions to treat these mental disorders. Here, we explore recent preclinical and clinical studies demonstrating the potential of using buprenorphine to treat major depressive disorder, treatment-resistant depression, and PTSD.MethodBibliographic databases were searched to include preclinical and clinical studies demonstrating the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 177 publications
0
11
0
Order By: Relevance
“…In the current experiments, we modeled prenatal opioid exposure in Sprague Dawley rats to demonstrate that buprenorphine exposure in utero can result in aberrant dopamine system function in adulthood. Buprenorphine, a partial μ-opioid receptor agonist, full κ-opioid and δ-opioid receptor antagonist, and full agonist at the NOP ( Kumar et al, 2014 ; Madison and Eitan, 2020 ), is the preferred treatment for opioid use disorder during pregnancy ( Bell et al, 2009 ; Women, Acog Committee on Health Care for Underserved, and Medicine American Society of Addiction, 2012 ; Mozurkewich and Rayburn, 2014 ). Maternal treatment with buprenorphine during pregnancy effectively reduces neonatal abstinence syndrome (NAS) and time spent in the hospital ( Jones et al, 2010 ), but gestational buprenorphine exposure has also been shown to result in childhood neurodevelopmental consequences similar to those of illicit opioid use during pregnancy ( Sundelin Wahlsten and Sarman, 2013 ; Sanchez et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current experiments, we modeled prenatal opioid exposure in Sprague Dawley rats to demonstrate that buprenorphine exposure in utero can result in aberrant dopamine system function in adulthood. Buprenorphine, a partial μ-opioid receptor agonist, full κ-opioid and δ-opioid receptor antagonist, and full agonist at the NOP ( Kumar et al, 2014 ; Madison and Eitan, 2020 ), is the preferred treatment for opioid use disorder during pregnancy ( Bell et al, 2009 ; Women, Acog Committee on Health Care for Underserved, and Medicine American Society of Addiction, 2012 ; Mozurkewich and Rayburn, 2014 ). Maternal treatment with buprenorphine during pregnancy effectively reduces neonatal abstinence syndrome (NAS) and time spent in the hospital ( Jones et al, 2010 ), but gestational buprenorphine exposure has also been shown to result in childhood neurodevelopmental consequences similar to those of illicit opioid use during pregnancy ( Sundelin Wahlsten and Sarman, 2013 ; Sanchez et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current experiments, we modeled prenatal opioid exposure in Sprague Dawley rats to demonstrate that buprenorphine exposure in utero can result in aberrant dopamine system function in adulthood. Buprenorphine, a partial μ-opioid receptor agonist, full κ-and δ-opioid receptor antagonist, and full agonist at the nociceptin opioid peptide receptor (NOP) (Madison and Eitan 2020;Kumar et al 2014), is the preferred treatment for opioid use disorder during pregnancy (Mozurkewich and Rayburn 2014; Women and American Society of Addiction 2012; Bell et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Methadone also affects repolarisation time of cardiomyocytes, which has been associated with risk of torsade de pointes [ 27 ]. Furthermore, buprenorphine can have a beneficial effect on mood and depression, due to its kappa-OR activity [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study was to investigate whether there were differential effects on opioid use among OUD patients with specific life-time psychiatric diagnoses (mood disorder, mental disorder other than mood disorder, none) who received MOUD with either methadone or buprenorphine. We focused upon mood disorder versus other mental disorders, because mood disorder is the most common mental disorder among this population and has been the most widely studied in relation to MOUD [16,17]. We hypothesized that OUD patients with mood disorder would have better outcomes (in terms of reductions in opioid use) if treated with buprenorphine, given its antidepressant effects associated with kappa antagonism, compared with outcomes of patients on methadone.…”
Section: Introductionmentioning
confidence: 99%
“…Opioid agonists have also been shown to act as psychotropic medicines in treating mental disorders, with beneficial effects in reducing mood, anxiety and psychotic symptoms [14,15]. Recently, there has been renewed interest in buprenorphine as a novel therapy for depression and other psychiatric disorders (PTSD) [16,17]. Buprenorphine, a partial μ-opioid receptor agonist and к-opioid receptor antagonist, has shown antidepressant properties [16,18], although supportive data of its effectiveness for depression are scarce.…”
Section: Introductionmentioning
confidence: 99%